TRADISI JUAL BELI BAJOJO DI JORONG KINAWAI NAGARI BALIMBING KABUPATEN TANAH DATAR DALAM TINJAUAN FIQH MUAMALAH - Vegi Melati; Syamsuwir Syamsuwir (Institut Agama Islam Negeri Batusangkar, 2021)
This study examines the review of fiqh muamalah on the tradition of buying and selling bajojo in jorong kinawai nagari balimbing, rambatan sub-district, Tanah flat district. The focus of the research is how to review muamalah fiqh on the tradition of buying and selling bajojo in Jorong Kinawai Nagari Balimbing, Rambatan District, Tanah Datar Regency. While the purpose of this study is to find out and explain how the fiqh muamalah view of the tradition of buying and selling bajojo in Jorong Kinawai Nagari Balimbing, Rambatan District, Tanah Datar Regency. This research is a field research. Data were obtained in 2 ways, namely secondary data and primary data. Primary data are traders and buyers (farmers), while secondary data sources are community leaders. After the data is collected, it is processed by means of interviews and analyzed by means of trigulation. This study found the results, namely the bajojo buying and selling tradition that occurred in Jorong Kinawai Nagari balimbing where the bajojo buying and selling tradition was a barter sale, goods exchanged for rice in this bajojo sale and purchase was a sale and purchase of dissimilar goods, based on the hadith which says that selling Buying barter must be buying and selling similar goods.